CASE STUDY: REVITALIZING THE CULTURE OF LOCAL WISDOM THROUGH EXTRACURRICULAR ACTIVITIES TO CREATE A STUDENT PROFILE OF PANCASILA - Sabrina Aulia Safitri; Feri Tirtoni (Jurnal Cakrawala Pendas, 2025)
Globalization has caused a cultural shift among the younger generation that has the potential to reduce the existence of local wisdom culture. Schools can make efforts to revitalize local wisdom culture through culture-based extracurricular activities so that cultural preservation is guaranteed. The objectives of this study are (1) to describe the process of implementing culture-based extracurricular activities; (2) to explain the components of the Pancasila student profile contained in the extracurricular activities of traditional dance, karawitan, and pencak silat; (3) to explain the inhibiting factors. This research was conducted at Hang Tuah 9 Elementary School in Candi Sidoarjo using qualitative methods and a case study approach. The research subjects included the principal, extracurricular coaches, and students. Data were collected through observation, interviews, and documentation which were analyzed using the Miles and Huberman model and verified using triangulation techniques. The results showed that there were three stages of implementation, namely planning, implementation, and evaluation.  This study also found that the revitalization of local wisdom culture through extracurricular traditional dance, karawitan, and pencak silat can form the profile of students who have the spirit of Pancasila. The research findings show that the activities not only increase students' appreciation of their cultural heritage, but also develop important character values such as obedience, responsibility, discipline, confidence, criticality, and accountability. However, the creative dimension was not found in this activity because learning is centered on the trainer's direction. The creative dimension is very important to develop the ability to create, innovate, and contribute in adapting or developing cultural values. In practice, this activity faces several obstacles such as time constraints, differences in student abilities, lack of supporting facilities, and parental concerns about pencak silat activities.